Health Workforce Planning in OECD Countries A Review of 26 Projection Models from 18 Countries - Ono, Tomoko (OECD Publishing, 2013)
Health workforce planning aims to achieve a proper balance between the supply and demand for different categories of health workers, in both the short and longer-term. Workforce planning in the health sector is particularly important, given the time and cost involved in training new doctors and other health professionals. In a context of tight budget constraints, proper health workforce planning is needed not only to guide policy decisions on entry into medical and nursing education programmes, but also to assess the impact of possible re-organisations in health service delivery to better respond to changing health care needs...
Keywords: Social Issues/Migration/Health